Media Sosial Sebagai Penjalin Hubungan antara Gereja dan Jemaat - Frimus Kennedy Hendarwin; Yugih Setyanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Through the development of existing technology, social media is very influential in human life. During this pandemic, the church has experienced a decline in its relationship with the congregation. With social media, it really helps the church in establishing relationships with congregations. Researchers conducted research on the use of church social media in establishing relationships with congregations. The purpose of this research is to find out how the church can utilize social media in establishing relationships with congregations. The theory used in this study is the theory of internal communication, community relations, new media, and social media. In this study, researchers used qualitative research methods by collecting data by means of interviews, observation and documentation. The results of this study indicate that GBI PRJ has carried out routine and active strategies in attracting congregations, social media as a means of communication and obstacles in establishing relationships with congregations. The conclusion of this research is that the application of social media that has been carried out is quite good in establishing relationships with the congregation because the church presents all information in full using an attractive design, and is clear in the information and captions conveyed as well as efforts to overcome obstacles that occur in the congregation regarding information social media use. Media sosial sangat berpengaruh dikehidupan manusia. Selama pandemi ini, gereja mengalami penurunan hubungan dengan jemaat. Keberadaan media sosial, sangat membantu gereja dalam menjalin hubungan dengan jemaat. Peneliti melakukan penelitian mengenai pemanfaatan media sosial gereja dalam menjalin hubungan dengan jemaat. Tujuan penelitian ini adalah untuk mengetahui bagaimana gereja bisa memanfaatkan media sosial dalam menjalin hubungan dengan jemaat. Teori yang digunakan dalam penelitian ini adalah teori komunikasi internal, community relations, new media, dan media sosial. Dalam penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan mengumpulkan data dengan cara wawancara, observasi dan dokumentasi. Hasil dari penelitian ini menunjukkan bahwa GBI PRJ telah melakukan strategi rutin dan aktif dalam menarik jemaat, media sosial sebagai sarana komunikasi dan hambatan dalam menjalin hubungan dengan jemaat. Kesimpulan dari penelitan ini adalah penerapan media sosial yang telah dilakukan sudah cukup baik dalam menjalin hubungan dengan jemaat karena gereja menyajikan semua informasi dengan lengkap dengan menggunakan desain yang menarik, dan jelas dalam informasi dan captions yang disampaikan serta upaya mengatasi hambatan yang terjadi pada jemaat mengenai info penggunaan media sosial.